2001
DOI: 10.1126/science.1064344
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Pancreatic Differentiation by Signals from Blood Vessels

Abstract: Blood vessels supply developing organs with metabolic sustenance. Here, we demonstrate a role for blood vessels as a source of developmental signals during pancreatic organogenesis. In vitro experiments with embryonic mouse tissues demonstrate that blood vessel endothelium induces insulin expression in isolated endoderm. Removal of the dorsal aorta in Xenopus laevis embryos results in the failure of insulin expression in vivo. Furthermore, using transgenic mice, we show that ectopic vascularization in the post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
831
4
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 981 publications
(861 citation statements)
references
References 19 publications
21
831
4
5
Order By: Relevance
“…We have indeed shown that taurine restored fetal islet vascularisation altered by an LP diet, as well as expression of IGF-2 and vascular endothelial growth factor [5,24]. Vascularisation and vascular endothelial growth factor are of prime importance for the differentiation of the endocrine pancreas [31], and IGFs, being mitogenic and survival factors, modulate the mass of islet cells [6,32]. Different levels of taurine during development may thus provide different populations of islet cells, resulting from an activity of this amino acid on these factors.…”
Section: Discussionmentioning
confidence: 59%
“…We have indeed shown that taurine restored fetal islet vascularisation altered by an LP diet, as well as expression of IGF-2 and vascular endothelial growth factor [5,24]. Vascularisation and vascular endothelial growth factor are of prime importance for the differentiation of the endocrine pancreas [31], and IGFs, being mitogenic and survival factors, modulate the mass of islet cells [6,32]. Different levels of taurine during development may thus provide different populations of islet cells, resulting from an activity of this amino acid on these factors.…”
Section: Discussionmentioning
confidence: 59%
“…For example, aorta-less Xenopus embryos failed to Developmental Dynamics express pancreatic genes, and co-culture of mouse dorsal prepancreatic endoderm with dorsal aortae could induce Pdx1 and insulin expression (Lammert et al, 2001). Furthermore, it was also shown that misexpression of VEGF-A (under a Pdx1 promoter) in transgenic mice caused islet hyperplasia and ectopic insulin þ cells in the stomach.…”
Section: Dorsal Pancreas Induction: Signaling From Notochord and Vascmentioning
confidence: 99%
“…[In mouse, some report that two ventral pancreas ''buds'' are first formed, with one regressing during gut rotation (Lammert et al, 2001), in association with the process of the dorsal to ventral pancreas joining that occurs at $E12.5.] Shortly after E9.5, the buds grow out into the adjacent mesenchyme, forming essentially ''solid buds'' of stratified epithelium.…”
Section: Pancreas Budding and The Primary Transitionmentioning
confidence: 99%
“…Evidence that endothelial cells are required for stem cell function comes from studies of developing islets of Langerhans and liver. The islets of Langerhans fail to develop in frogs in which the dorsal aorta has been ablated (27). Similarly, liver fails to develop in mice in which blood vessels do not develop (28).…”
Section: Discussionmentioning
confidence: 99%
“…The failure of development of these organs in the absence of blood vessels occurs at a time before blood begins to flow, suggesting that the failure of development is not the result of a lack of blood-derived nutrients, but due to the absence of endothelial-derived signals. Signals from the blood vessels induce the ectopic development of islets of Langerhans in developing gut (27), and overgrowth of the liver (29). Additional evidence that blood vessels are important for stem cell function comes from studies of neuronal stem cells.…”
Section: Discussionmentioning
confidence: 99%